2016
DOI: 10.1016/j.meatsci.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Inter-laboratory assessment by trained panelists from France and the United Kingdom of beef cooked at two different end-point temperatures

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…The sensory attributes of the analyzed breeds fell within the range described by most authors (Campo, Sañudo, Panea, Albertí, & Santolaria, ; Campo et al, ; Ciria, Asenjo, Beriain, & Gorraiz, ; Gagaoua et al, ; Gorraiz, Beriain, Chasco, & Insausti, ; Guerrero et al, ; Olleta et al, ; Panea et al, ; Serra et al, ). In the literature, there is not a clear consensus about a breed effect on the sensory quality of meat.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The sensory attributes of the analyzed breeds fell within the range described by most authors (Campo, Sañudo, Panea, Albertí, & Santolaria, ; Campo et al, ; Ciria, Asenjo, Beriain, & Gorraiz, ; Gagaoua et al, ; Gorraiz, Beriain, Chasco, & Insausti, ; Guerrero et al, ; Olleta et al, ; Panea et al, ; Serra et al, ). In the literature, there is not a clear consensus about a breed effect on the sensory quality of meat.…”
Section: Discussionsupporting
confidence: 71%
“…Comparison between laboratories is difficult in sensory analysis. Gagaoua et al () in an interlaboratory study with different types of animals and two endpoint temperatures, found that tenderness and juiciness scores were lower at the higher internal end‐point cooking temperature, independent of the sensory protocol used whereas the endpoint temperature effect on beef flavor depended on lab conditions. Nevertheless, in the current experiment, interlaboratory comparison was not possible because each laboratory worked only at one endpoint temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were presented in sequential monadic sessions involving 12 panellists. The expert panellists were trained in accordance with the ISO standards ISO/TC 34 as described by Gagaoua et al . Thus, the panellists rated global tenderness of the grilled meat on a 10‐cm unstructured line scale (from 0 to 10), where 0 refers to extremely tough and 10 to extremely tender meat.…”
Section: Methodsmentioning
confidence: 99%
“…For tenderness evaluation, the sensory protocol recently described by our group was used . Briefly, the steaks aged for 14 days were thawed at 5 °C for 48 h before cooking and sensory assessment at 55 °C, which end‐point cooking temperature that is usually employed in France . One hour before sensory assessment, the meat samples were cut into steaks (thickness of approximately 1.50 cm) and grilled on a double grooved plate griddle (SOFRACA, Morangis, France) heated to 300 °C for 30 min before cooking.…”
Section: Methodsmentioning
confidence: 99%